Analysis of Price Perceptions, Product Quality and Location on Purchasing Decisions for Kenangan Coffee at the Binjai Store - Nst, Muhammad Yusuf Hidayah; Ritonga, Husni Muharram; Sanny, Annisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of price perceptions, product quality and location on purchasing decisions at Kopi Kenangan. A quantitative approach was used with accidental sampling technique and the sample size was 99 respondents, calculated using the Slovin formula. Data were analyzed using multiple linear regression with SPSS. The results show that price and location perceptions have a significant effect on purchasing decisions, while product quality does not show a significant effect. The F test confirms that simultaneously, these three variables have a significant effect on purchasing decisions